Benzer a criação: sobre bichos, animais e benzimentos em Itaju/SP - Stefanuto, Míriam Rebeca Rodeguero (Universidade Federal de São Carlos, 2024)
This research focus on studying catholic blessing practices used in the municipality of Itaju, within the Jaú region of São Paulo state, Brazil. Specifically, it examined the procedures conducted to heal or protect the livestock animals, primarily cattle and pigs. The investigation relied both on pertinent literature analysis and field research with benedictors, livestock breeders and people with varying beliefs in the blessing practices. The aim was to investigate the blessing practices as a technique used in animal husbandry and understand its functioning in daily rural life of animal breeders. The practice of benediction involves learning through both gift and faith of all participants. In addition, animal breeders present it as a facilitator of rural work, integrating it as an active component in daily life with livestock. When considering benedictions, it became necessary to explore the consequences of this gift that some people have. This includes the expectation that benedictors ideally refrain from charging for their services and may use them exclusively for beneficial purposes. Additionally, since animals and others resources on farms are considered divine gifts, humans are authorized to enjoy these resources with a certain authority. Analyses of whom benedictions oppose and whom they aim to protect have revealed some distinctions between types of creatures, as “bicho” and “animal”: although both are creations of God, the “animal” creatures have the unique status of being created twice, by God and by humans, as livestock. In such cases, they are the most protected through benediction against snakes and “bicho” creatures, often perceived as pests. Therefore, the benediction works as a technique to protect livestock against certain animals and represent a facilitation in the work on rural properties that encompasses elements of catholic religiosity.
Blessing the animal husbandry: about beasts, animals, and blessings in Itaju/SP
Keywords: Benzimento; Catolicismo; Técnica; Animais; Bichos; Benediction; Catholicism; Technique; Animals; Bichos; CIENCIAS HUMANAS::ANTROPOLOGIA::ANTROPOLOGIA RURAL